Discussion on the Application of Water Environment Treatment and Three-water Separation Project in Shenzhen - TANG Yawen; CHEN Wangwang (Renmin Zhujiang)
To fulfill the overall requirement of long-term cleanliness and sustainable development of the water environment in Shenzhen,this paper investigates the Longgang River Basin Water Environment Management Project to propose a general three-water separation plan that integrates “closed sewage system,open rainwater system,and efficient interception system”.Tracing to the source and diversion of key outlets and sewage interception transformation are carried out to release the clean base flow,drive the sewage system to be relatively independent from the initial light rain system,and ultimately to slow down non-point source pollution,improve the quality and efficiency of the sewage treatment plant,and strengthen the operation and maintenance scheduling of the pipe network system.With the implementation of the three-water separation project,the influent biochemical oxygen demand (BOD) concentration of the sewage treatment plant in the Longgang River Basin is significantly lower than that in 2019 after the second half of 2020.Therefore,applying the three-water separation project to water environment treatment is essential for fulfilling the assessment requirements on water control and quality improvement in Shenzhen and accomplishing relevant construction tasks.